Brain activation and functional connectivity in premanifest Huntington's disease during states of intrinsic and phasic alertness - Wolf, Robert Christian; Wolf, Nadine D.; Thomann, Philipp (Human brain mapping, 2012)
Previous functional neuroimaging studies have shown brain activation abnormalities in clinically presymptomatic carriers of the Huntington's disease (preHD) gene mutation when performing complex cognitive tasks. However, little is known about the neural correlates of attentional processes in preHD. In this study, we used functional magnetic resonance imaging to investigate basic aspects of attentional processing in preHD individuals (n = 18) compared to healthy participants (n = 18) during an alertness task. Uni- and multivariate statistical techniques were used to assess task-related regional brain activation and functional network connectivity. Compared to healthy controls, preHD individuals near to the estimated onset of clinical signs showed lower activation of right frontostriatal regions during phasic alertness (P < 0.001, uncorrected). Decreased striatal activation in this preHD subgroup was also evident when compared with those preHD individuals far from the estimated onset of HD signs. Lower putaminal activity was associated with longer reaction times and with proximity to onset. In addition, preHD participants near to onset had lower functional connectivity of motor regions when compared with controls and preHD individuals far from onset. Our data suggest that while alertness-related performance remains normal, the underlying frontostriatal activity and motor cortex connectivity decline only when approaching the onset of unequivocal signs of HD. However, these attentional network changes might not be the sole explanation for the differences in cognitive task performance previously observed in preHD. Hum Brain Mapp 33:2161-2173, 2012. © 2011 Wiley Periodicals, Inc.